The Mediating Effect of Islamic Marketing Capabilities in The Relationship Between Entrepreneurial Orientation And Firm Performance at Handicraft SMEs In West Java - Hendayana, Yayan; Puspaningtyas Faeni, Dewi; El-Kafafi, Siham (UPT Publikasi Ilmiah UNISBA, 2024)
The purpose of this study is to determine the influence of entrepreneurial orientation and market orientation on Islamic marketing capabilities and their impact on the performance of SMEs in the handicraft sector in West Java. The population in this study is the managers of leather craft SMEs with a sample of 160 respondents using the purposive sampling method. Data analysis using the help of SmartPLS program. The results showed that entrepreneurial orientation had a significant positive effect on Islamic marketing ability, Islamic marketing ability had a significant positive effect on SME performance, and Islamic marketing ability mediated the influence of entrepreneurial orientation on the performance of SMEs in the leather handicraft sector in West Java. The results of this study recommend to SMEs in the handicraft sector in West Java to continue to improve entrepreneurial orientation to support the improvement of the ability to market their products, so that overall business performance continues to grow.